2016
DOI: 10.1021/acs.jpcc.6b02657
|View full text |Cite
|
Sign up to set email alerts
|

Indium Oxide Thin Films by Atomic Layer Deposition Using Trimethylindium and Ozone

Abstract: We investigated the atomic layer deposition (ALD) of indium oxide (In2O3) thin films using alternating exposures of trimethylindium (TMIn) and a variety of oxygen sources: ozone (O3), O2, deionized H2O, and hydrogen peroxide (H2O2). We used in situ quartz crystal microbalance measurements to evaluate the effectiveness of the different oxygen sources and found that only O3 yielded viable and sustained In2O3 growth with TMIn. These measurements also provided details about the In2O3 growth mechanism and enabled u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
58
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 80 publications
9
58
2
Order By: Relevance
“…Figure 1 c shows that the growth rate was directly dependent on the deposition temperature, increasing with temperature with no separate temperature window within which a constant growth rate was observed, as reported earlier with other conditions [ 23 , 24 ]. Otherwise, our results are inconsistent with the previous reports; ALD-deposited In 2 O 3 thin film with TMIn with ozone and TEIn with ozone was proposed in ALD process windows between 100 and 200 °C [ 29 , 31 ] and others [ 28 ]. Figure 1 c shows that the growth rate of In 2 O 3 increased drastically from 0.009 nm/cycle to 0.035 nm/cycle at a growth temperature of 115 to 150 °C.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Figure 1 c shows that the growth rate was directly dependent on the deposition temperature, increasing with temperature with no separate temperature window within which a constant growth rate was observed, as reported earlier with other conditions [ 23 , 24 ]. Otherwise, our results are inconsistent with the previous reports; ALD-deposited In 2 O 3 thin film with TMIn with ozone and TEIn with ozone was proposed in ALD process windows between 100 and 200 °C [ 29 , 31 ] and others [ 28 ]. Figure 1 c shows that the growth rate of In 2 O 3 increased drastically from 0.009 nm/cycle to 0.035 nm/cycle at a growth temperature of 115 to 150 °C.…”
Section: Resultscontrasting
confidence: 99%
“…It is also shown that the indium possesses 3 + valency states in the In 2 O 3 lattice structure in all the growth temperatures. Our findings are consistent with the previous reports for ALD-In 2 O 3 using other precursors [ 24 , 25 , 29 , 30 ].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Regarding the C 1 s XPS spectra shown in Fig. 4a, the film deposited at 160 °C displays a peak at 289.8 eV, which should correspond to C-O [21]. When the deposition temperature is increased to 180 °C, the peak becomes much weaker.…”
Section: Resultsmentioning
confidence: 99%